(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the Islamic language units used in the socio-political lexicon of Alisher Navoi’s work "Mahbub ul-Qulub" are researched and explained through examples. Currently, the importance of these words and their correct use are explained with analytical materials based on examples.